Conducting Interviews for News Stories - Ricky W. Telg (EDIS)
In order to write a good news story for print, television, or radio, you have to conduct interviews with the people who have the information you need. An interview is the process of asking good questions so you can get good answers for your news story. This 3-page fact sheet provides some tips to follow as you conduct a news story interview. Written by Ricky Telg, and published by the UF Department of Agricultural Education and Communication, January 2015. (Photo: VStock/Thinkstock.com)